Students' Perception of Comfort in Using Air Conditioning at Tunku Tun Aminah Library - Mohd Jamil, Muhammad Khairi Afiq; Liew Abdullah, Nurul Hidayah (Research and Innovation in Technical and Vocational Education and Training, 2025)
Malaysia has a hot and humid climate throughout the year, making air conditioning a necessity in buildings. The Tunku Tun Aminah Library (PTTA) is a key learning center for students at Universiti Tun Hussein Onn Malaysia (UTHM), providing air conditioning facilities to enhance user comfort. This study aims to identify students' perceptions of the comfort of using air conditioning at PTTA in terms of air quality and health. A quantitative approach was used, with a survey conducted among 387 respondents. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 27. The findings indicate that students' perception of air quality is moderate, while their perception of health effects is low. The study suggests that PTTA should improve temperature control and indoor environment quality to enhance student comfort and learning quality.